Cartilage repair scaffold and preparation method thereof
By constructing a charge gradient structure in the cartilage repair scaffold, and combining it with collagen, heparin sulfate, and chondroitin sulfate to form a three-dimensional porous structure, the problem of the difficulty in simulating the structure of natural cartilage tissue in existing technologies is solved. This achieves the synergistic effect of inflammation regulation, growth factor enrichment, and directional cell distribution, thereby improving the cartilage damage repair effect.
Patent Information
- Application Number
- CN202610382776.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-03-26
- Publication Date
- 2026-06-23
AI Technical Summary
Existing biomimetic cartilage scaffolds cannot simultaneously achieve inflammation suppression, growth factor enrichment, and cell stratification within the same material system, and therefore cannot simulate the structural characteristics of natural cartilage tissue.
A cartilage repair scaffold is designed, comprising a surface anti-inflammatory functional layer and a deep regeneration promoting layer. A charge gradient structure is constructed by introducing heparin sulfate into the surface layer and chondroitin sulfate into the deep layer. Combined with collagen and platelet-rich plasma, a three-dimensional porous structure is formed, and autologous biological components are loaded to achieve synergistic effects.
It achieves a synergistic effect of inflammation regulation, growth factor enrichment and directed cell distribution, simulates the biophysical environment of natural cartilage tissue, and improves the cartilage damage repair effect.
Smart Images

Figure CN122251701A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of tissue engineering materials technology, and in particular to a cartilage repair scaffold and its preparation method. Background Technology
[0002] Articular cartilage is a highly specialized connective tissue, primarily composed of chondrocytes and the extracellular matrix. Cartilage tissue exhibits a distinct layered structure, with significant differences in structural composition and biological function across different layers. For example, superficial collagen fibers are arranged in parallel and possess high lubrication, while deeper collagen fibers are arranged vertically and have higher load-bearing capacity. Simultaneously, the content of proteoglycans and glycosaminoglycans (GAGs) in cartilage tissue shows a gradient distribution, and the overall charge density gradually increases from the surface to the deeper layers, thus forming a stable biomechanical environment. However, articular cartilage tissue lacks a vascular, nerve, and lymphatic system, and its self-repair capacity is extremely limited once damaged. Trauma or degenerative changes lead to the destruction of the cartilage matrix structure and induce local inflammatory responses.
[0003] Therefore, how to effectively regulate the inflammatory microenvironment in the early stages of cartilage repair while promoting cartilage regeneration is an important research direction in the field of cartilage tissue engineering.
[0004] In recent years, the application of platelet-rich plasma (PRP) and stromal vascular fraction (SVF) in cartilage repair has gradually attracted attention. PRP is a high-concentration platelet preparation obtained through centrifugation, rich in various growth factors. These growth factors can regulate inflammation-related signaling pathways in cartilage and synovial cells, promoting cell proliferation and cartilage matrix synthesis; however, their effects are easily interfered with by the inflammatory microenvironment. SVF, on the other hand, is a cell population isolated from adipose tissue through mechanical or enzymatic methods. It includes adipose-derived mesenchymal stem cells (ADSCs), vascular endothelial cells, pericytes, and various immunomodulatory cells. Under appropriate conditions, it can differentiate into chondrocyte-like cells and secrete various growth factors and immunomodulatory factors, promoting extracellular matrix synthesis and regulating local inflammatory responses. Therefore, the combined application of PRP and SVF in cartilage repair has the potential to synergistically promote tissue regeneration.
[0005] To synthesize biomimetic cartilage scaffolds that possess both stable material properties and multiple biological functions, researchers have designed various scaffold structures. However, in existing technologies, most studies mainly use simple PRP or SVF mixed with materials such as collagen, which makes it difficult to simultaneously achieve multiple functions such as inflammation suppression, growth factor enrichment, and cell stratification and localization in the same material system, and thus cannot simulate the structural characteristics of natural cartilage tissue.
[0006] In view of this, how to provide a biomimetic cartilage repair scaffold system that can simultaneously achieve charge gradient regulation, growth factor enrichment, and rapid intraoperative loading of PRP and SVF is a technical problem that urgently needs to be solved. Summary of the Invention
[0007] To address the problem that existing biomimetic cartilage scaffolds cannot simulate the structural characteristics of natural cartilage tissue, this invention provides a cartilage repair scaffold that achieves synergistic control of inflammation and regeneration through high negative charge GAG and PRP / SVF, thus solving the problem that existing biomimetic cartilage scaffolds cannot simulate the structural and charge gradient characteristics present in natural cartilage tissue.
[0008] The technical solution adopted by this invention to solve its technical problem is: A cartilage repair scaffold includes a superficial anti-inflammatory functional layer and a deep regeneration promoting layer, wherein: The surface anti-inflammatory functional layer is composed of collagen, platelet-rich plasma, heparin sulfate and hyaluronic acid; The deep regeneration promoting layer is composed of collagen, platelet-rich plasma, adipose-derived matrix vascular component cells, hyaluronic acid, and chondroitin sulfate.
[0009] Optionally, in the surface anti-inflammatory functional layer, the collagen has a mass concentration of 1.5 wt% to 3.0 wt%; the platelet enrichment coefficient in the platelet-rich plasma is 1 to 3 times; the concentration of heparin sulfate is 50 to 150 µg / mL; and the concentration of hyaluronic acid is 0.3 wt% to 0.8 wt%.
[0010] Optionally, the collagen concentration in the deep regeneration promoting layer is 3.0 wt% to 5.0 wt%; the platelet enrichment coefficient in the platelet-rich plasma is 3 to 6 times; and the cell concentration of the fat-derived matrix vascular components is... The concentration of the hyaluronic acid is 0.2 wt% to 0.5 wt%; the concentration of the chondroitin sulfate is 0.2 wt% to 0.8 wt%.
[0011] Optionally, the cartilage repair scaffold has a three-dimensional porous structure with a wet porosity of 80% to 95%.
[0012] Optionally, the pore size of the surface anti-inflammatory functional layer is 50–150 µm, and the pore size of the deep regeneration promoting layer is 150–300 µm.
[0013] Optionally, the thickness of the cartilage repair scaffold is 2 to 5 mm.
[0014] Optionally, the thickness of the surface anti-inflammatory functional layer is 0.5–1.5 mm, and the thickness of the deep regeneration promoting layer is 1.5–3.5 mm.
[0015] Another object of the present invention is to provide a method for preparing the cartilage repair scaffold as described above, comprising the following steps: According to the formula, collagen is dissolved in a weakly acidic solution to form a collagen solution, and collagen solutions for the surface material and the deep material are prepared separately. Hyaluronic acid and heparin sulfate are added to the collagen solution of the surface material to form a first precursor solution; Hyaluronic acid and chondroitin sulfate are added to the collagen solution of the deep material to form a second precursor solution; The second precursor liquid is injected into the bottom of the mold and pre-frozen. The first precursor liquid is then added to the upper part of the mold to form a surface material system; The mold was frozen and then sublimated and dried to obtain a cartilage repair scaffold.
[0016] Optionally, the freezing temperature range is -20℃ to -80℃.
[0017] Optionally, the sublimation drying process is carried out under vacuum conditions at a pressure of 5–30 Pa.
[0018] The beneficial effects of this invention are: The cartilage repair scaffold provided by this invention introduces heparin sulfate into the material system of the surface anti-inflammatory functional layer and chondroitin sulfate into the material system of the deep regeneration promoting layer, so that the cartilage repair scaffold forms a gradually changing anionic glycosaminoglycan content gradient from the surface to the deep layer, thereby constructing a bilayer porous structure with charge gradient characteristics to achieve the synergistic effect of inflammation regulation, growth factor enrichment and cell directional distribution. Attached Figure Description
[0019] The present invention will be further described below with reference to the accompanying drawings and embodiments.
[0020] Figure 1 These are mechanical property test diagrams of the cartilage repair scaffolds prepared according to various embodiments and comparative examples of the present invention; Figure 2 The effects of the cartilage repair scaffolds prepared in the various embodiments and comparative examples of this invention on cell proliferation; Figure 3 The expression of COL2 in cartilage tissue differentiation experiments of the cartilage repair scaffolds prepared in various embodiments and comparative examples of the present invention; Figure 4This refers to the expression of Aggrecan in cartilage tissue differentiation experiments using cartilage repair scaffolds prepared in various embodiments and comparative examples of the present invention. Detailed Implementation
[0021] The present invention will now be described in further detail. The embodiments described below are exemplary and intended to explain the present invention, and should not be construed as limiting the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.
[0022] To address the problem that existing biomimetic cartilage scaffolds cannot mimic the structural characteristics of natural cartilage tissue, this invention provides a cartilage repair scaffold. This cartilage repair scaffold has a biomimetic double-layer porous structure, specifically comprising a surface anti-inflammatory functional layer and a deep regeneration promoting layer. The surface anti-inflammatory functional layer is composed of collagen, platelet-rich plasma, heparin sulfate, and hyaluronic acid; the deep regeneration promoting layer is composed of collagen, platelet-rich plasma, adipose-derived matrix vascular component cells, hyaluronic acid, and chondroitin sulfate.
[0023] This cartilage repair scaffold constructs a charge gradient structure using glycosaminoglycan components. Specifically, the anionic glycosaminoglycans in the surface anti-inflammatory functional layer are mainly composed of heparin sulfate, while the anionic glycosaminoglycans in the deep regeneration promoting layer are mainly composed of chondroitin sulfate. This creates a charge microenvironment that gradually changes from the surface to the deep layer, enabling the material to accumulate PRP-derived growth factors and regulate inflammatory factor signaling pathways.
[0024] The cartilage repair scaffold provided by this invention introduces heparin sulfate into the material system of the surface anti-inflammatory functional layer and chondroitin sulfate into the material system of the deep regeneration promoting layer, so that the cartilage repair scaffold forms a gradually changing anionic glycosaminoglycan content gradient from the surface to the deep layer, thereby constructing a bilayer porous structure with charge gradient characteristics to achieve the synergistic effect of inflammation regulation, growth factor enrichment and cell directional distribution.
[0025] The present invention preferably describes a cartilage repair scaffold as a three-dimensional porous structure formed by freeze-drying, which has an interconnected pore structure and can be loaded with autologous platelet-rich plasma and fat-derived matrix vascular component cells to form a cartilage regeneration composite system during use.
[0026] Furthermore, in the preferred anti-inflammatory functional layer of the present invention, the collagen concentration is 1.5 wt% to 3.0 wt%; the platelet enrichment coefficient in platelet-rich plasma is 1 to 3 times; the concentration of heparin sulfate is 50 to 150 µg / mL; and the concentration of hyaluronic acid is 0.3 wt% to 0.8 wt%.
[0027] This surface material system forms a glycosaminoglycan network with a high negative charge density through heparin sulfate and hyaluronic acid, thereby enhancing the adsorption capacity for inflammatory factors and growth factors, and regulating the local inflammatory microenvironment through the growth factors released by low-concentration PRP.
[0028] The present invention preferably includes a collagen concentration of 3.0 wt%–5.0 wt% in the deep regeneration promoting layer; a platelet enrichment coefficient of 3–6 times in platelet-rich plasma; and a cell concentration of fat-derived matrix vascular components of [missing information]. The concentration of hyaluronic acid is 0.2 wt% to 0.5 wt%; the concentration of chondroitin sulfate is 0.2 wt% to 0.8 wt%.
[0029] This deep material system forms a mechanical support structure through a high concentration of collagen, provides abundant growth factors through PRP, and provides stem cell sources through SVF cells to promote cartilage matrix formation.
[0030] The present invention preferably has a three-dimensional porous structure for cartilage repair scaffold, and preferably has a wet porosity of 80% to 95%.
[0031] Specifically, the present invention preferably has a surface anti-inflammatory functional layer with a pore size of 50-150 µm and a deep regeneration promoting layer with a pore size of 150-300 µm to promote cell migration and nutrient exchange.
[0032] The present invention further preferably has a cartilage repair scaffold thickness of 2-5 mm, and further preferably has a surface anti-inflammatory functional layer thickness of 0.5-1.5 mm and a deep regeneration promoting layer thickness of 1.5-3.5 mm, in order to simulate the layered structure of natural articular cartilage tissue.
[0033] Another object of the present invention is to provide a method for preparing the cartilage repair scaffold as described above, the method comprising the following steps: According to the formula, dissolve the collagen in a weakly acidic solution to form a uniform collagen solution, and prepare separate collagen solutions for the surface layer and the deep layer. Hyaluronic acid and heparin sulfate were added to the collagen solution of the surface material and mixed evenly to form the first precursor solution; Specifically, in preparing the first precursor solution, hyaluronic acid is added to the collagen solution and stirred at low temperature to ensure complete dissolution. Then, heparin sulfate solution is added and stirring continues to mix, so that the components are evenly dispersed, thereby forming the surface material precursor solution, i.e., the first precursor solution. Hyaluronic acid and chondroitin sulfate are added to the collagen solution of the deep material and mixed evenly to form a second precursor solution; Specifically, in preparing the second precursor solution, hyaluronic acid is dissolved in a collagen solution, and then chondroitin sulfate is added and thoroughly mixed to form a deep material precursor solution, namely the second precursor solution. The second precursor liquid is injected into the bottom of the mold to form a deep material system, and pre-frozen at low temperature to allow the solution to initially form a stable structure; the volume and thickness in the mold are controlled as needed (usually 50% to 70% of the total thickness). Then, the first precursor liquid is slowly added to the upper part of the mold so that it covers the deep material system and forms the surface material system, thus forming a double-layer material structure. After layering, the mold is subjected to a programmed cooling and freezing process to form an integral structure between the surface and deep layers. Through the ice crystal formation process, a porous structure is built inside the material. After freezing, the material is placed in a vacuum freeze-drying device and then sublimated. During the freeze-drying process, the ice crystals sublimate and form an interconnected pore structure inside the material, thereby obtaining a two-layer collagen scaffold with a three-dimensional porous structure. Finally, the cartilage repair scaffold is obtained through aseptic processing.
[0034] Specifically, after freeze-drying, the stent can be sterilized, for example, using ethylene oxide sterilization or... Radiation sterilization is used to obtain the final cartilage repair scaffold product.
[0035] The present invention preferably freezes the material at a temperature range of -20°C to -80°C, and preferably freezes it for 4 to 24 hours. The sublimation drying process is preferably carried out under vacuum conditions at a pressure of 5 to 30 Pa, and preferably dries for 24 to 72 hours. By controlling the freezing rate and freeze-drying parameters, an interconnected porous structure is formed inside the support.
[0036] The cartilage repair scaffold provided by this invention, when used clinically, can form a composite cartilage repair material by loading autologous biological components during surgery, specifically including the following steps: First, high-concentration platelet-rich plasma is mixed with lipid-derived vascular component cells to form a cell suspension, which is then loaded into the deep regeneration promotion layer of the scaffold, allowing the cell suspension to infiltrate the deep region through the scaffold channels. Subsequently, low-concentration platelet-rich plasma was loaded into the anti-inflammatory functional layer of the stent surface; The stratified positioning of biological components in the scaffold is achieved through capillary action and pore structure. Specifically, due to the interconnected pore structure and the hydrophilicity of the material, liquid can be evenly distributed inside the scaffold through capillary action, thereby achieving the stratified positioning of PRP and SVF cells in the scaffold.
[0037] Thus, this invention provides a bilayered, charge-gradient, lyophilized porous scaffold constructed based on collagen and glycosaminoglycans (GAGs). During use, autologous platelet-rich plasma (PRP) and stromal vascular fraction (SVF) are loaded to form a cartilage repair composite material with layered function and initial mechanical support. This invention introduces GAGs into the cartilage repair material and constructs a layered structure with a charge gradient. By constructing a GAGs-rich anti-inflammatory factor enrichment layer on the surface and a regenerative support layer containing SVF cells in the deeper layer, it achieves synergistic promotion of inflammation regulation and cartilage regeneration. It can simulate the biophysical environment present in natural cartilage tissue and simultaneously realize the synergistic effect of inflammation regulation and regeneration promotion.
[0038] In summary, this invention provides a cartilage repair scaffold with a charge gradient layered structure. This scaffold, by constructing a biomimetic bilayer structure and combining it with anionic glycosaminoglycan materials to regulate charge distribution, achieves a synergistic effect of inflammation regulation, growth factor enrichment, and cartilage regeneration promotion, thereby improving the cartilage damage repair effect. Its initial form is a collagen-GAG bilayer freeze-dried scaffold with a charge gradient of high negative charge on the surface and low negative charge in the deep layer. The high-charge GAG can effectively regulate the diffusion of inflammatory factors and cellular responses. During surgery, PRP and SVF are loaded to form a layered functional complex to promote cartilage regeneration, thereby improving the cartilage defect repair effect and achieving synergistic control of inflammation and regeneration by high-negative-charge GAG and PRP / SVF.
[0039] The cartilage repair scaffold provided by this invention has a three-dimensional porous structure, prepared using a freeze-drying process. Structurally, it comprises a surface anti-inflammatory functional layer and a deep regeneration-promoting layer. The two layers are integrally connected via a collagen network, forming a continuous and stable porous scaffold structure. By controlling the glycosaminoglycan components and their content in both layers, a gradually changing anionic charge density is created from the surface to the deeper layers of the scaffold, thereby constructing a biomimetic microenvironment with charge gradient characteristics. This charge gradient structure promotes the stable adsorption and slow release of PRP growth factors, while simultaneously regulating inflammatory factor signaling pathways, thereby improving cartilage regeneration efficiency.
[0040] Compared with existing technologies, the cartilage repair scaffold provided by this invention has a surface layer of highly negatively charged GAGs that can adsorb inflammatory mediators and delay their spread, resulting in more effective inflammation regulation; a deep layer of high PRP + SVF provides continuous and efficient growth factors and differentiateable cells, promoting more comprehensive regeneration; the separation of inflammation control and regeneration promotion pressures better meets the needs of physiological repair, and the functional stratification is more clearly defined; it is also closer in composition to cartilage ECM, has good biocompatibility, and strong biomimetic properties.
[0041] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings.
[0042] Unless otherwise specified, the collagen in the embodiments and comparative examples of this invention was prepared according to the following method: S1: Take fresh pig skin tissue, fragment it to obtain particles with a diameter of 2mm-5mm, soak and clean it with physiological saline, then soak it in 0.1M sodium hydroxide solution for 20 minutes, repeat the process 3 times to obtain skin tissue after preliminary impurity removal; wash the skin tissue after preliminary impurity removal with purified water until the pH is close to neutral, then add 5% sodium carbonate solution at a weight of 5 times the weight of pig skin to the pig skin, keep the solution temperature ≤25℃, soak it twice, changing the solution in between, and each soaking time is not less than 1 hour, to perform degreasing treatment to obtain pretreated skin tissue.
[0043] S2: Add an acid solution (0.5M acetic acid solution, with a mass ratio of 50:1 between the acid solution and the pretreated skin tissue) to the pretreated skin tissue at 7℃ for 48 hours. Emulsify the tissue gel twice to achieve homogenization. Then add pepsin, with a final enzyme concentration of 0.08% in the tissue homogenate, and hydrolyze at 4℃ for 60 hours, stirring during this period to promote complete hydrolysis of the skin tissue. Adjust the pH of the hydrolyzed gel to the neutral range, and then add sodium chloride in two steps for salting out. The specific addition process is as follows: First salting out: Prepare a final concentration of 1.3M NaCl, slowly add NaCl while stirring the mixed gel for 1 hour to precipitate collagen. After stirring, let it stand for 1 hour (ambient temperature 4-10℃) until the collagen fibers separate from the solution. Use a 60-mesh nylon filter to drain the extract in each container and collect the precipitate. Second salting out: The collected collagen fibers (half the original volume) were reconstituted with 0.5M acetic acid solution, the pH was adjusted to about 7, and NaCl was added to a final concentration of 1.0M. The solution was then drained and filtered once more, and the collagen precipitate from the second salting out was collected to obtain a collagen solution.
[0044] S3: Dilute the collagen solution to 0.4 mg / mL with a 0.1 M acetic acid solution pre-cooled to 4 °C. At this point, the viscosity will decrease significantly, not exceeding 10 mPa·s, to obtain the diluted collagen solution. S4: Slowly add 0.05M sterile NaCl solution pre-cooled to 4°C to the diluted collagen solution, and gently stir for 12 minutes to obtain the collagen solution to be purified.
[0045] S5: Purification with weak cation exchange resin: Purification was performed using D152 macroporous weakly acidic cation exchange resin at pH 4-5. Pre-equilibration of the column: The column was washed with equilibration buffer (20 mM acetate-sodium acetate buffer (pH 5.5)) until the UV absorbance was close to baseline or stable. Sample loading: The sample was loaded slowly at a flow rate of 1 BV / h. Elution: A linear gradient was used to increase the elution strength in the eluent, eluting substances with different binding strengths from the column. Different fractions were collected, and the location of the target product was determined. Regeneration: The column was washed with equilibration buffer containing a high concentration of salt (e.g., 2 M NaCl) to obtain purified collagen.
[0046] S6: The purified collagen solution, after... After sterile filtration, a sterile, high-purity collagen solution is obtained. After freeze-drying using sterile freeze-drying equipment, sterile collagen powder is obtained.
[0047] The cartilage repair scaffolds in each embodiment of the present invention are prepared according to the following method: For the surface anti-inflammatory functional layer, heparin sulfate and sodium hyaluronate were weighed and dissolved in a small amount of sterile water. After filtration through a 0.22 µm filter membrane, a high-concentration stock solution was prepared and then slowly added to the collagen system. The final concentrations of collagen, heparin sulfate, and hyaluronic acid in the system are shown in Table 1. The addition process required slow dripping with continuous gentle stirring to ensure thorough mixing with the collagen, forming a homogeneous composite solution, i.e., the first precursor solution.
[0048] For the deep regeneration promoting layer, chondroitin sulfate and sodium hyaluronate were weighed and dissolved in a small amount of sterile deionized water, and then added to the collagen solution above. The final collagen concentration, chondroitin sulfate concentration, and final hyaluronic acid concentration are shown in Table 1. The mixture was then slowly stirred at 4°C for 5 hours to ensure uniform dispersion of chondroitin sulfate in the collagen solution, thus forming the second precursor solution.
[0049] After mixing, the first and second precursor solutions were degassed separately by centrifugation at 2000 rpm for 5 min to remove air bubbles and ensure a uniform pore structure in the final scaffold. The second precursor solution was then quantitatively dispensed into a polytetrafluoroethylene (PTFE) mold, with the volume and thickness controlled as needed. The dispensed samples were first placed at 4°C for 15 min to allow initial stabilization, then transferred to -20°C for pre-freezing for 3 h to allow the solution to gradually form ice crystals. The first precursor solution was then slowly added to the top of the mold, covering the deeper material system, and transferred to -80°C for further freezing for 10 h to stabilize the ice crystal template.
[0050] After complete freezing, the samples were transferred to a freeze dryer for lyophilization. Sublimation drying was performed under vacuum conditions, with the cold trap temperature set at -50°C for approximately 48 hours, allowing the ice crystals in the system to sublimate and form a three-dimensional porous structure. Upon completion of lyophilization, a white or off-white sponge-like collagen / GAG composite scaffold was obtained.
[0051] Intraoperative loading of PRP and SVF: The prepared collagen / GAG lyophilized composite scaffold was loaded with cells and growth factors under aseptic conditions. First, the lyophilized scaffold was placed in a clean bench, and its surface was gently moistened with sterile PBS buffer to restore partial water absorption and remove air from the scaffold, thereby improving the subsequent infiltration efficiency of the cell suspension. The moistening time was generally 4 minutes. Excess liquid was then blotted away with sterile filter paper, keeping the scaffold moist but not completely saturated.
[0052] Subsequently, deep cell loading was performed. A pre-prepared high-concentration PRP was mixed with SVF cell suspension to form a deep composite suspension. The PRP platelet enrichment coefficient and SVF cell concentration are shown in Table 1. The scaffold was placed in a low-absorption culture plate, and the cells were loaded using a pipette. A large volume of deep composite suspension is slowly dripped to the bottom of the scaffold or the lower layer of the scaffold, allowing the solution to gradually penetrate the scaffold's pore structure through capillary action. The culture plate is then placed at 4°C and allowed to stand for 12 minutes to ensure that the deep solution fully wets the larger pore areas inside the scaffold.
[0053] After deep cell loading is completed, the surface functional layer is constructed. A low-concentration PRP solution (platelet enrichment coefficient shown in Table 1) is prepared as a surface infiltration solution, which is then applied using a micropipette. The volume of PRP is evenly added to the upper surface area of the scaffold. The infiltrated scaffold is placed in a 37°C incubator and left to stand for 25 minutes, allowing the fibrin in the PRP to gradually form a gel structure, thereby fixing the PRP and SVF cells in the scaffold pore network, resulting in a cartilage repair scaffold.
[0054] Table 1 Comparative Example 1 This comparative example provides a cartilage repair scaffold, which differs from Example 1 in that its composition is as follows: Surface layer: Collagen 2.0 wt%, PRP (2×), HA 0.5 wt%; Deep layer: Collagen 4.0 wt%, PRP (5×). HA 0.5 wt%.
[0055] Comparative Example 2 This comparative example provides a cartilage repair scaffold, which differs from Example 1 in that its composition is as follows: Surface layer: Collagen 2.0 wt%, PRP (3×), Heparin sulfate 100 µg / mL, HA 0.5 wt% Deep layer: Collagen 4.0 wt%, PRP (3×). HA 0.5 wt%, chondroitin sulfate 0.3 wt%.
[0056] Comparative Example 3 This comparative example provides a cartilage repair scaffold, which differs from Example 1 in that its composition is as follows: Surface layer: Collagen 2.0 wt%, PRP (2×), Heparin sulfate 100 µg / mL, HA 0.5 wt% Deep layer: Collagen 4.0 wt%, PRP (5×), HA 0.5 wt%, chondroitin sulfate 0.3 wt%.
[0057] In the embodiments and comparative examples of the present invention, the thickness of the surface anti-inflammatory functional layer is 1 mm, and the thickness of the deep regeneration promoting layer is 2 mm.
[0058] The performance of the cartilage repair scaffolds prepared in each embodiment and comparative example was tested using the following methods: 1. Zeta potential detection To characterize the surface charge properties of the scaffold material of this invention, Zeta potential was measured on samples from various embodiments and comparative examples. The freeze-dried scaffold samples were removed, and the surface and deep layers of material were cut off. The resulting materials were subjected to cryogenic grinding under liquid nitrogen conditions to form uniformly sized microparticles. Approximately 10 mg of sample powder was weighed and added to 10 mL of deionized water, and ultrasonically dispersed at room temperature for 10 min to ensure thorough dispersion and the formation of a stable suspension. The suspension was then placed in an oscillator and oscillated at 200 rpm for 30 min to promote sufficient contact between the material and the solvent and to form a stable colloidal system. To eliminate the influence of particle aggregation on the measurement results, the suspension was ultrasonically treated again for 5 min. A suitable amount of the sample suspension was then transferred to a Zeta potential testing cell and measured using a laser particle size and Zeta potential analyzer. The detection temperature was set to 25℃, and each sample was measured three times, with the average value taken. The test results are shown in Table 2.
[0059] Table 2 Zeta potential measurements were performed on the surface scaffolds. The results showed that all scaffolds in each embodiment exhibited significant negative charge. The Zeta potential of Example 1 reached -35.8 mV, significantly higher than the comparative group, indicating that the introduction of heparin sulfate significantly enhanced the negative charge density on the material surface. Comparative Example 1, lacking heparin sulfate, had a surface mainly composed of collagen and hyaluronic acid, resulting in a Zeta potential of only -12.4 mV. Comparative Examples 2 and 3, although incorporating some GAGs, lacked a charge gradient structure, resulting in a Zeta potential of only approximately -20 mV. Example 5, with a further increase in heparin sulfate concentration, achieved a Zeta potential of -45.6 mV; however, excessively high negative charge could lead to excessive water absorption and swelling, thus affecting the overall structural stability.
[0060] The zeta potential of the deep material is generally lower than that of the surface material, indicating that this invention successfully constructs a negative charge gradient structure that gradually decreases from the surface to the deep layers. In Example 1, the zeta potential of the deep material is -24.7 mV, forming a charge gradient difference of approximately 11 mV with the surface layer. This charge gradient can effectively promote the accumulation of growth factors and provide a suitable microenvironment for cell adhesion and differentiation. In Comparative Example 1, since no charge stratification is formed, the potential difference between the surface and deep layers is smaller, indicating that the overall charge structure of the material is more uniform. Although Example 5 has higher negative charge, its charge gradient difference is smaller, therefore its overall functional performance is not as good as that of Example 1.
[0061] The above results indicate that Embodiment 1 of the present invention can form a stable and moderate charge gradient structure, which is beneficial to achieving the synergistic effect of inflammation regulation and cartilage regeneration.
[0062] 2. Mechanical property experiments To verify the mechanical properties of the prepared bilayer osteochondral tissue repair scaffold material, wet compressive modulus and compressive strength testing methods were selected to test the bilayer osteochondral tissue repair scaffold samples prepared in the above examples and comparative examples. After freeze-drying, each group of prepared collagen composite scaffolds was cut into cylindrical specimens with a diameter of 8 mm and a height of 4 mm using a cylindrical punch. Before testing, all samples were placed in phosphate buffered saline (PBS) at pH 7.4 and kept at a constant temperature of 37°C for 12 h to balance the water absorption, simulating the wet environment within the joint cavity and allowing the scaffolds to reach a stable hydration state. After removing the samples, excess liquid was gently absorbed from the surface with filter paper, and mechanical property testing was immediately performed. Wet compression testing was conducted using an Instron 5943 Universal Testing Machine. The scaffold samples were placed between upper and lower parallel compression plates, and uniaxial unconstrained compression testing was performed at room temperature with a loading rate set to 1 mm / min. During the test, the stress-strain curve was recorded in real time. When the sample was compressed to 10% strain, the wet compressive modulus was calculated based on the slope of the linear interval of the stress-strain curve from 5% to 10%. When compression continued to 60% strain or when the sample structure showed significant damage, the maximum stress value in the stress-strain curve was recorded, and this maximum stress value was defined as the compressive strength of the support. Five parallel samples were set up for each experimental group. The experimental results are expressed as mean ± standard deviation. The test results are shown in Table 3. Figure 1 As shown.
[0063] Table 3 The experimental results show a comparison of the compressive modulus of different collagen composite scaffold formulations under wet conditions. The results indicate that the overall mechanical properties of the scaffold in this invention are significantly better than those in the comparative groups. Specifically, Example 1 achieved a wet compressive modulus of 320 kPa, the highest among all experimental groups. In Comparative Example 1, the lack of a charge gradient structure in both the surface and deep layers, coupled with the uniform distribution of chondroitin sulfate and hyaluronic acid within the scaffold, resulted in weak electrostatic interactions between collagen fibers, leading to decreased overall network stability and a compressive modulus of only 120 kPa. Although Comparative Example 2 introduced a charge gradient structure, the uniform PRP concentration in both the surface and deep layers reduced the density of the fibrin network within the scaffold, resulting in an unstable collagen-fibrin composite network structure and a compressive modulus of 145 kPa. Comparative Example 3 lacked SVF cell sources, resulting in less extracellular matrix secretion and weakened structural reinforcement within the scaffold, leading to a compressive modulus of 135 kPa. In contrast, Example 1 significantly improved the structural stability and compressive strength of the material by constructing a negative charge gradient structure formed by a surface layer of heparin sulfate and a deep layer of chondroitin sulfate, while simultaneously introducing high concentrations of PRP and SVF cells into the deep layer, thus creating a stable three-dimensional collagen-GAG-fibrin composite network within the scaffold. Example 2, by reducing collagen concentration, increased the scaffold porosity but simultaneously weakened the mechanical support of the collagen fiber network, resulting in a reduced compressive modulus of 240 kPa. Example 3 enhanced structural strength by increasing collagen concentration, achieving a compressive modulus of 300 kPa; however, due to reduced porosity, the overall structural uniformity was slightly worse, thus still lower than Example 1. Example 4 enhanced the scaffold's hydration capacity and increased material flexibility by increasing hyaluronic acid content, but excessive hydration reduced material stiffness, resulting in a modulus of 260 kPa. Example 5, although increasing the heparin sulfate and chondroitin sulfate content enhanced the negative charge density, the excessively high GAG content led to increased water absorption and swelling, resulting in a slightly lower compressive modulus than Example 1.
[0064] The above results indicate that Example 1 achieved an optimal balance between collagen concentration, GAG content, PRP concentration, and cell load, resulting in the scaffold exhibiting optimal mechanical properties.
[0065] 3. Cell proliferation assay This experiment will detect scaffold cell viability using the CCK-8 assay. First, an extract of the scaffold material is prepared, and then… 2.0 g of sterile double-layer osteochondral repair scaffold material sterilized by radiation was added to 10 mL of complete hMSC culture medium and extracted at 37°C for 72±2 h to obtain a scaffold extract with a concentration of 200 mg / mL. At 37°C, hBMSCs were cultured at a concentration of 5.0%. When the second-generation hBMSCs reached 70% confluence, 3 mL of trypsin (using a pore size of...) was injected. The solution was digested using membrane filtration. Cells were seeded at a density of [missing information] in 96-well cell culture plates, with [missing information] cells seeded per well. After incubating the cell culture plates containing cells in an incubator for 24 hours, the culture medium was aspirated. Six wells were then used as a parallel sample group. The control group used... Cells were cultured in complete culture medium, while the experimental group used... Cells were cultured using an extract of the scaffold material. After culturing for 1, 3, 5, and 7 days, the culture medium was aspirated, and the scaffold material was added to each well. The solution at 37°C After incubation in an incubator for 2 hours, the samples were removed. Readings at 450 nm were measured using a microplate reader. Results are shown in Table 4. Figure 2 As shown.
[0066] Table 4 Experimental results show that the scaffold material of this invention can significantly promote cell proliferation. Comparative Example 1, lacking a charge gradient structure, had a weaker ability to immobilize growth factors, resulting in slower cell proliferation. Comparative Example 2, with its uniform PRP concentration and lack of surface anti-inflammatory and deep regenerative functional differentiation, had limited improvement in cell proliferation. Comparative Example 3, without the addition of SVF cells, showed a significant decrease in extracellular matrix synthesis. Example 1, by constructing a triple synergistic structure of PRP concentration gradient + charge gradient + SVF cells, significantly improved cell adhesion and proliferation, achieving an OD value of 1.358 on day 7, the highest among all groups. Example 2, due to the high porosity of the material, showed a slightly higher cell proliferation rate in the early stage of culture (Day 3), but with prolonged culture time, the final cell number was slightly lower than in Example 1 due to insufficient mechanical stability of the material. Example 3, due to the high collagen concentration, decreased porosity, limiting cell migration, thus reducing cell proliferation. Example 5, due to excessively high negative charge density, affected the adsorption of cell adhesion proteins, resulting in a slightly lower cell proliferation rate.
[0067] 4. Chondrocyte differentiation detection experiment To evaluate the promoting effect of the prepared bilayer collagen / GAG composite scaffold on chondrogenesis, the expression of chondrogenesis-related genes in the cells within the scaffold was detected. First, the composite scaffold loaded with PRP and SVF cells was placed in a 24-well cell culture plate, and 1 mL of chondrogenesis induction medium (DMEM medium containing 10% fetal bovine serum, 1% penicillin and streptomycin, and appropriate amounts of other ingredients) was added to each well. Place the culture plate at 37℃. The cultures were incubated in a constant temperature incubator, with the culture medium changed every 2–3 days. Samples were taken on days 7, 14, and 21 of culture to detect the expression levels of cartilage-specific genes.
[0068] During sample collection, the scaffold was first gently washed three times with PBS buffer to remove any culture medium residue. Then, the scaffold was cut into small pieces using sterile scissors, and an appropriate amount of TRIzol reagent was added to lyse the sample. The sample was then thoroughly shaken to disrupt the scaffold structure and release cellular RNA. Total RNA was then extracted according to the RNA extraction kit instructions, and RNA purity and concentration were determined using a UV spectrophotometer. Total RNA was reverse transcribed to synthesize cDNA. Subsequently, real-time quantitative PCR (qPCR) was used to detect the expression of cartilage-related genes, including type II collagen (COL2A1) and Aggrecan (ACAN), with GAPDH as an internal control gene. The PCR reaction system was as follows: The reagents included SYBR Green qPCR Mix, specific primers, template cDNA, and nuclease-free water. The PCR reaction conditions were: 95℃ pre-denaturation for 5 min; followed by 40 cycles (95℃ for 15 s, 60℃ for 30 s).
[0069] Experimental results adopted The relative expression levels of cartilage-specific genes in each group of samples were calculated and compared with those in the control group. If the expression of COL2A1 and ACAN was significantly upregulated in the composite scaffold group, it indicates that the bilayer scaffold structure can effectively promote the differentiation of SVF cells into chondrocytes and facilitate the formation of extracellular matrix in chondrocytes.
[0070] The test results are shown in Table 5 and Figure 3 , Figure 4 As shown.
[0071] Table 5 The results of the chondrocyte differentiation experiments showed that the scaffold of the present invention significantly promoted chondrocyte phenotypic expression. In Example 1, the expression levels of COL2 and Aggrecan reached 4.40 and 5.30, respectively, the highest among all experimental groups, indicating that the structure can effectively promote the formation of hyaline cartilage matrix. Comparative Example 1 had lower COL2 and Aggrecan expression levels due to the lack of a charge gradient structure. Although Comparative Example 2 constructed a charge environment, its PRP concentration was 3-fold enriched in both the surface and deep layers, and no PRP concentration gradient structure was formed. The expression level was slightly higher than that of Comparative Example 1, but still significantly lower than that of the Example groups. In Comparative Example 3, no SVF cells were added, and the COL2 expression level was only 0.80, the lowest among all experimental groups. At the same time, Aggrecan expression also decreased significantly, indicating that SVF plays a key role in cartilage regeneration. In Example 2, the reduced collagen concentration led to decreased material structural stability, thus affecting the long-term cell differentiation environment. In Example 3, the higher collagen concentration limited cell migration and nutrient diffusion, thereby affecting chondrocyte differentiation efficiency. Example 4 showed good biocompatibility due to the increased hyaluronic acid content (0.7 wt% in the surface layer and 0.4 wt% in the deeper layer). However, the excessively high hyaluronic acid content may reduce the stability of the internal network structure of the material, thereby affecting cell differentiation efficiency, and the expression level was slightly lower than that in Example 1. In Example 5, the excessively high negative charge density may affect the adsorption of cell adhesion proteins, thereby reducing cell adhesion efficiency.
[0072] 5. Inflammatory factor detection experiment To evaluate the ability of cartilage repair scaffolds to regulate the inflammatory microenvironment, the anti-inflammatory effect of the scaffolds was assessed by detecting the levels of inflammatory factors in the culture system. In the experiment, a composite scaffold loaded with PRP and SVF cells was placed in a 24-well culture plate and 1 mL of complete culture medium was added for incubation. To simulate the inflammatory environment following cartilage injury, an appropriate amount of lipopolysaccharide (LPS, final concentration...) was added to the culture system. Inducing an inflammatory response. The experiment was divided into an example group (double-layer composite scaffold), a comparative group (single-layer collagen scaffold), and a blank control group. Culture conditions were 37℃. Incubator.
[0073] Culture supernatant was collected on days 1, 3, and 7 for inflammatory factor detection. During collection, the culture plate was gently shaken, the supernatant was aspirated, and centrifuged at 3000 rpm for 10 min at 4°C to remove suspended cells and debris. The supernatant was then transferred to new centrifuge tubes and stored at -80°C for later use. Inflammatory factor detection was performed using enzyme-linked immunosorbent assay (ELISA), and the detected indicators included... , And IL-6. Following the ELISA kit instructions: First, add the standards and samples to a 96-well plate pre-coated with antibody and incubate at 37°C for 1 h; then add the biotinylated detection antibody and incubate for another 30 min; after washing the plate, add HRP-labeled streptavidin and incubate for another 30 min; finally, add TMB chromogenic substrate for reaction, and after color development, add stop solution to terminate the reaction. Measure the absorbance at 450 nm using a microplate reader. Calculate the concentration of inflammatory factors in each sample based on the standard curve, and perform statistical analysis on different experimental groups.
[0074] The test results are shown in Table 5.
[0075] Table 5 The results of the inflammatory factor detection experiment showed that due to the release of PRP Anti-inflammatory factors such as heparin sulfate can inhibit inflammatory responses. SVF cells have immunomodulatory functions and can promote macrophage polarization towards the M2 type. At the same time, heparin sulfate forms a negatively charged environment, which can adsorb inflammatory factors and reduce their local concentration. Therefore, the concentration of inflammatory factors in Example 1 is the lowest. , The concentrations of IL-6 cytokine in Example 2 were only 34.5 pg / mL, 41.6 pg / mL, and 58.2 pg / mL, respectively, demonstrating the best anti-inflammatory effect. In the comparative examples, due to the lack of charge gradient structures or anti-inflammatory functional layers, the expression of inflammatory factors was higher. In Example 2, the decreased collagen concentration led to weakened growth factor fixation, resulting in a slightly higher inflammation level than in Example 1. In Example 3, the excessively high collagen concentration affected cell migration and the diffusion of anti-inflammatory factors, resulting in a higher inflammation level than in Example 1. In Example 4, hyaluronic acid had lubricating and anti-inflammatory effects, resulting in a lower inflammation level, but still slightly higher than in Example 1. In Example 5, excessively high negative charge may have affected cell adhesion, resulting in a higher level of inflammatory factors.
[0076] Based on the above-described preferred embodiments of the present invention, and through the foregoing description, those skilled in the art can make various changes and modifications without departing from the inventive concept. The technical scope of this invention is not limited to the contents of the specification, but must be determined according to the scope of the claims.
Claims
1. A cartilage repair scaffold, characterized in that, It includes a surface anti-inflammatory functional layer and a deep regeneration promoting layer, wherein: The surface anti-inflammatory functional layer is composed of collagen, platelet-rich plasma, heparin sulfate and hyaluronic acid; The deep regeneration promoting layer is composed of collagen, platelet-rich plasma, adipose-derived matrix vascular component cells, hyaluronic acid, and chondroitin sulfate.
2. The cartilage repair scaffold as described in claim 1, characterized in that, In the surface anti-inflammatory functional layer, the collagen concentration is 1.5 wt% to 3.0 wt%; the platelet enrichment coefficient in the platelet-rich plasma is 1 to 3 times; the concentration of heparin sulfate is 50 to 150 µg / mL; and the concentration of hyaluronic acid is 0.3 wt% to 0.8 wt%.
3. The cartilage repair scaffold as described in claim 1, characterized in that, The collagen concentration in the deep regeneration promoting layer is 3.0 wt%–5.0 wt%; the platelet enrichment coefficient in the platelet-rich plasma is 3–6 times; and the cell concentration of the fat-derived matrix vascular components is… The concentration of the hyaluronic acid is 0.2 wt% to 0.5 wt%; the concentration of the chondroitin sulfate is 0.2 wt% to 0.8 wt%.
4. The cartilage repair scaffold as described in any one of claims 1-3, characterized in that, The cartilage repair scaffold has a three-dimensional porous structure with a wet porosity of 80% to 95%.
5. The cartilage repair scaffold as described in claim 4, characterized in that, The surface anti-inflammatory functional layer has a pore size of 50–150 µm, and the deep regeneration promoting layer has a pore size of 150–300 µm.
6. The cartilage repair scaffold as described in claim 4, characterized in that, The thickness of the cartilage repair scaffold is 2-5 mm.
7. The cartilage repair scaffold as described in claim 4, characterized in that, The thickness of the surface anti-inflammatory functional layer is 0.5–1.5 mm, and the thickness of the deep regeneration promoting layer is 1.5–3.5 mm.
8. A method for preparing a cartilage repair scaffold as described in any one of claims 1-7, characterized in that, Includes the following steps: According to the formula, collagen is dissolved in a weakly acidic solution to form a collagen solution, and collagen solutions for the surface material and the deep material are prepared separately. Hyaluronic acid and heparin sulfate are added to the collagen solution of the surface material to form a first precursor solution; Hyaluronic acid and chondroitin sulfate are added to the collagen solution of the deep material to form a second precursor solution; The second precursor liquid is injected into the bottom of the mold and pre-frozen. The first precursor liquid is then added to the upper part of the mold to form a surface material system; The mold was frozen and then sublimated and dried to obtain a cartilage repair scaffold.
9. The method for preparing the cartilage repair scaffold as described in claim 8, characterized in that, The freezing temperature range is -20℃ to -80℃.
10. The method for preparing the cartilage repair scaffold as described in claim 8, characterized in that, The sublimation drying process is carried out under vacuum conditions at a pressure of 5–30 Pa.